Contiguous RNA editing sites in the mitochondrial nad1 transcript of Arabidopsis thaliana are recognized by different proteins. Issue 7 (14th February 2013) - Arenas-M, Anita; Takenaka, Mizuki; Moreno, Sebastián; Gómez, Isabel; Jordana, Xavier
Abstract : Pentatricopeptide repeat (PPR) proteins have been identified as site‐specific factors for RNA editing in plant organelles. These proteins recognize cis ‐elements near the editing site. It is unclear how contiguous sites are addressed, and whether one or two factors are required. We here show the PPR MEF25 to be essential for RNA editing at the nad1 ‐308 site in Arabidopsis mitochondria. Another editing site just one nucleotide upstream, nad1 ‐307, is edited normally in mef25 mutant lines. This finding shows that two independent factors recognizing similar cis ‐elements are involved at these contiguous sites without competing with each other in vivo. Abstract : ► At3g25060 encodes an E+‐subclass pentatricopeptide repeat (PPR) protein in Arabidopsis thaliana . ► AT3G25060 is an editing factor targeted to mitochondria (Mitochondrial Editing Factor, MEF25). ► MEF25 specifically addresses one of two contiguous RNA editing sites in the nad1 transcript. ► Two adjacent RNA editing sites must be recognized by at least two different editing factors. ► Lack of editing in mef25 mutants changes a conserved amino acid in NADH dehydrogenase subunit 1.